2020
DOI: 10.1111/ans.15998
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative and intra‐operative chemical thromboprophylaxis increases bleeding risk following elective cholecystectomy: a multicentre (PROTECTinG) study

Abstract: Background: Cholecystectomy is commonly performed in general surgery. Despite guidelines recommending chemical thromboprophylaxis in the perioperative period, the most appropriate time for its initiation is unknown. Here, we investigated whether timing of chemoprophylaxis affected venous thromboembolism (VTE) and bleeding rates postcholecystectomy. Methods: Retrospective review of all elective cholecystectomies performed between 1 January 2018 and 30 June 2019, across seven Victorian hospitals. Clinical VTE wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…Unfortunately, such an approach can lead to inadequate protection against VTE or increase post-operative bleeding risk. 4 In this study, we extend the observations made from our multicentre survey by quantifying the heterogeneity of perioperative thromboprophylaxis across all major general surgical operations, and placing them in context of their bleeding and VTE risk. Findings from this study will highlight areas of practice with the greatest variability, allow surgeons to benchmark their practices against that of their colleagues and focus future research to optimize perioperative thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Unfortunately, such an approach can lead to inadequate protection against VTE or increase post-operative bleeding risk. 4 In this study, we extend the observations made from our multicentre survey by quantifying the heterogeneity of perioperative thromboprophylaxis across all major general surgical operations, and placing them in context of their bleeding and VTE risk. Findings from this study will highlight areas of practice with the greatest variability, allow surgeons to benchmark their practices against that of their colleagues and focus future research to optimize perioperative thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 74%
“…Variable use of chemoprophylaxis was most commonly seen in surgeries on the neck, breast, gall bladder and ventral hernias. This may be explained by their inherently low but not absent VTE risk, their relatively higher although not exceedingly high rate of postoperative bleeding, [4][5][6][7] discrepant literature which encourages yet questions the need for chemoprophylaxis, 8 confusing guidelines which broadly recommends chemoprophylaxis without accounting for individual risks 2 and a fear of litigation which may influence decision-making. 9 Importantly, chemoprophylaxis use has been associated with increased bleeding in these operations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in patients undergoing elective cholecystectomies, early chemoprophylaxis has been associated with increased rates of bleeding compared with its post-operative usage. 5 Moreover, findings from the Victorian Audit of Surgical Mortality identified that inappropriate use of thromboprophylaxis repeatedly contributed to surgical mortality. 6 Chemoprophylaxis requires balancing the risk of bleeding with thromboembolic protection.…”
mentioning
confidence: 99%